CEMARAN TELUR CACING Soil Transmitted Helminths (STH) PADA DAUN BAYAM, KANGKUNG DAN SAWI YANG DIJUAL DI PASAR - Soraya, Soraya; Hidayat, Nurohmat; Ramadhan, Algi Rifalgi (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2024)
Soil Transmitted Helminths (STH) is a round intestinal worm that in its lifecycle occurs outside the human body with its main medium of transmission, namely soil, and is widespread in tropical and subtropical regions. Kecacingan is a disease that infects many people, more than 1.5 billion people (24%) of the world’s population. This study aimed o find out how much Soil Transmitted Helminths (STH) contamination in the leaves of kale spinach, and mustard. This study is descriptive with the sedimentation technique method using a 0.2% NaOH solution for sample examination with sample number 36. The results of the study found that 44.4% (16 samples) contaminated with STH worm eggs were found Ascaris lumbricoides from 3 (18.75%) samples of spinach leaves and 6 (37.5%) samples of kale leaves by (Ascaris lumbricoides, Trichuris trichiura and sp hookworm eggs). And 7 (43.75%) samples of mustard leaves by Ascaris lumbricoides the remaining 55.5% (20 samples) negatively found Soil Transmitted Helminths (STH) worm egg types. So we conclude that the prevalence of Soil Transmitted Helminths (STH) eggs is moderate from the data that has been obtained. The results of this study can strengthen the assumption that the a high number of cases of diarrhea in the district of Kiaracondong, one of which is due to spinach, kale, and mustard leaves contaminated with STH worm eggs.